Recent advances and perspectives on natural latex serum and its fractions for biomedical applications - Herculano, Rondinelli Donizetti [UNESP]; Mussagy, Cassamo Ussemane; Guerra, Nayrim Brizuela [UNESP]; Sant'Ana Pegorin Brasil, Giovana [UNESP]; Floriano, Juliana Ferreira [UNESP]; Burd, Betina Sayeg [UNESP]; Su, Yanjin [UNESP]; da Silva Sasaki, Josana Carla [UNESP]; Marques, Paulo Augusto Chagas; Scontri, Mateus [UNESP]; Miranda, Matheus Carlos Romeiro; Ferreira, Ernando Silva; et al. (Elsevier, 2024)
Advances and the discovery of new biomaterials have opened new frontiers in regenerative medicine. These biomaterials play a key role in current medicine by improving the life quality or even saving the lives of millions of people. Since the 2000s, Natural Rubber Latex (NRL) has been employed as wound dressings, mechanical barrier for Guided Bone Regeneration (GBR), matrix for drug delivery, and grafting. NRL is a natural polymer that can stimulate cell proliferation, neoangiogenesis, and extracellular matrix (ECM) formation. Furthermore, it is well established that proteins and other biologically active molecules present in the Natural Latex Serum (NLS) are responsible for the biological properties of NRL. NLS can be obtained from NRL by three main methods, namely (i) Centrifugation (fractionation of NRL in distinct fractions), (ii) Coagulation and sedimentation (coagulating NRL to separate the NLS from rubber particles), and (iii) Alternative extraction process (elution from NRL membrane). In this review, the chemical composition, physicochemical properties, toxicity, and other biological information such as osteogenesis, vasculogenesis, adhesion, proliferation, antimicrobial behavior, and antitumoral activity of NLS, as well as some of its medical instruments and devices are discussed. The progress in NLS applications in the biomedical field, more specifically in cell cultures, alternative animals, regular animals, and clinical trials are also discussed. An overview of the challenges and future directions of the applications of NLS and its derivatives in tissue engineering for hard and soft tissue regeneration is also given.
Keywords: Alternative animals; Biomaterials; Chorioallantoic membrane; Fractions; Natural latex serum; Tissue regeneration